O giro ambiental e o cinema hollywoodiano: um estudo de caso a partir do filme Avatar - Silveira, Ludmila Carneiro da (2020)
The cinematographic narrative is a space for the (re) production of ideas on various themes of society, and nature is an important issue used recurrently in Hollywood cinematographies. The message of James Cameron's Avatar film is clear, human societies need to preserve and respect nature. The research seeks to understand how the idea about nature are explored in the story of Avatar, where the research aims to read the film through the lens of environmental history and from the decolonial approach, problematizing these speeches related to the idea of nature and preservation of nature.